Interesting mycoparasites and Paradingleyomyces lepidopterorum gen. et sp. nov. (Hypocreales, Polycephalomycetaceae) from Yunnan Province, China - Yi Wang; De-Ping Wei; Xing-Can Peng; Ji-Chuan Kang; Zeng-Zhi Li; Chun-Ru Li; Xian Zhang; Gui-Ying Wang; Yun Zhou; Xin-Sheng He; Putarak Chomnunti; Ting-Chi Wen (MycoKeys)
A novel genus, Paradingleyomyces was introduced to accommodate Pa. lepidopterorum sp. nov., based on a multigene phylogenetic analysis and its distinct morphological characteristics. Maximum likelihood (ML) and Bayesian inference analyses (BI) of ITS, SSU, LSU, tef-1α, rpb1, and rpb2 sequence data shown that Pa. lepidopterorum formed an independent lineage nested between Perennicordyceps and Dingleyomyces. Morphologically, Paradingleyomyces is distinguished from Perennicordyceps by the presence of a white subiculum on the stromata of Ophiocordyceps cf. cochlidiicola. Perithecia are produced sporadically from the base to the apex of the stromata, and the secondary ascospores exhibit a notable length-to-width ratio. These characteristics distinguish Paradingleyomyces from Perennicordyceps which exhibits tortuous, branched, clavate to cylindrical stromata with rhizomorphs, parasitism of coleopteran and hemipteran larvae, and colonizes a broader range of fungal hosts. Additionally, perithecia in Perennicordyceps typically arise from the middle to the upper regions of the stromata, with secondary ascospores displaying a comparatively lower length-to-width ratio. Paradingleyomyces is morphologically identical to Dingleyomyces in its direct production of superficial perithecia on the stromata of Ophiocordyceps species. However, the phylogenetic analysis indicates that Paradingleyomyces and Dingleyomyces are not congeneric. Moreover, this study introduces another novel species, Polycephalomyces tengchongensis, and a novel sexual morph of Pleurocordyceps yunnanensis. Dimorphic phialides and conidia of Pleurocordyceps parvicapitata were observed and described for the first time based on a fresh collection from Tengchong County, Yunnan Province, China.